2003
DOI: 10.1183/09031936.03.00041703
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes with major histocompatibility complex class II and co-stimulatory molecules are present in human BAL fluid

Abstract: Exosomes are 30-100 nm diameter vesicles formed by inward budding of endosomal compartments and are produced by several cell types, including T-cells, Bcells and dendritic cells (DC)s. Exosomes from DCs express major histocompatibility complexes (MHC) class I and II, and co-stimulatory molecules on their surface, and can induce antigen-specific activation of T-cells.The aims of the present study were to investigate for the presence of exosomes in bronchoalveolar lavage fluid (BALF) from healthy individuals, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
258
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(261 citation statements)
references
References 27 publications
3
258
0
Order By: Relevance
“…It has been reported that exosomes secreted by APC contain large amounts of MHC class I (MHC-I) and II (MHC-II) molecules, as well as detectable levels of certain costimulatory molecules [8,9,12]. MHC antigens have been widely applied as a marker of APC-derived exosomes [13,14]. However, most of the above reports have utilized cell lines or cultured primary cells and the results obtained from these in vitro systems may not reflect the situation observed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that exosomes secreted by APC contain large amounts of MHC class I (MHC-I) and II (MHC-II) molecules, as well as detectable levels of certain costimulatory molecules [8,9,12]. MHC antigens have been widely applied as a marker of APC-derived exosomes [13,14]. However, most of the above reports have utilized cell lines or cultured primary cells and the results obtained from these in vitro systems may not reflect the situation observed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have been identified in plasma, 13 urine, 14 malignant effusions 15 and bronchoalveolar lavage fluid. 16 It is likely that the esRNA is mediating communication in a microenvironment, but the presence of exosomes in serum may suggest that this type of genetic communication theoretically could occur also at a distance. It has been shown that mast cell derived exosomes are able to induce maturation of DCs by upregulation of MHCII, CD40, CD80 and CD86 17 or exosomes from antigen presenting cells are involved in T-cell stimulation both in vitro 18 and in vivo.…”
Section: The Putative Roles Of Exosomal Shuttle Rnamentioning
confidence: 99%
“…All cells produce and release exosomes, which are often found in different body fluids such as plasma (8), serum (9, 10) malignant ascites (11,12) urine (13), amniotic fluid (14), bronchoalveolar lavage fluid (15,16), and breast milk (17,18). Recent studies suggest however that cancer cells produce exosomes, which may be differentiated from those derived from normal cells primarily based upon their cargo.…”
mentioning
confidence: 99%